Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Genre, migrations et globalisation de la reproduction sociale - Verschuur, Christine; (Dir), Christine Catarino; Par, Dirigé. (L'Harmattan, 2013)
Les études féministes ont souligné l’importance d’étudier le travail auparavant invisible des femmes, productif et reproductif, et la nouvelle division du travail productif et reproductif dans la mondialisation du capitalisme. L’analyse du capitalisme mondialisé dans une perspective décoloniale permet de comprendre qu’il n’est pas seulement un système économique ni seulement un système culturel mais un réseau global de pouvoir intégré par des processus économiques, politiques et culturels qui constituent un ensemble. Partout on observe un système, social, économique, culturel, moral d’organisation de la reproduction sociale, y compris le care, entendu comme échange économico-affectif, qui implique des biens et des services liés à l’économie capitaliste. Dans le nouvel ordre économique global, que l’on pourrait toujours qualifier de colonial, caractérisé par la nouvelle division internationale du travail, l’articulation entre rapports sociaux dans l’économie domestique et capitaliste prend de nouvelles formes. Mais le système repose toujours sur l’organisation de l’ensemble des activités et des rapports indispensables à la reproduction sociale, par-delà les frontières, dans des réseaux et foyers transnationaux, en s’appuyant sur des discours de genre et de race, voire de classe. Dans ce système, les femmes migrantes sont particulièrement présentes. Elles constituent un maillon essentiel du système de protection sociale aux Nords, y contribuent à la production de richesses, tout en assurant l’organisation de la reproduction sociale aux Suds, dans les foyers qu’elles ont gardés dans leurs pays d’origine.
Keywords: approches et analyses; capitalisme; care; cours; discipline; féminisme décolonial; globalisation; intersectionnalité; justice sociale; militance; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences humaines; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; travail; travail du sexe